The Effect Of Village Financial Management And Internal Control System On APBDES Accountability (Empirical Study of Villages in Pamulihan District, Sumedang Regency) - Nurfitriyani, Novita; Kartika, Tita (LPPM Universitas Sebelas April, 2024)
Accountability must be realized in the financial management of the village government, so that all village government activities can be accounted to the community. One that can support the success of APBDes accountability is the existence of a good internal control system within the village government. This study aims to determine the effect of village financial management and internal control system on APBDes accountability. This research was conducted using quantitative methods with primary data. The data collection technique in this study used a questionnaire with a sample number of 44 respondents determined using purposive sampling techniques. The results of this study show that village financial management variables have a positive and significant effect on the accountability of APBDes with a GIS value of 0.000 < 0.05. The internal control system has a positive and significant effect on the accountability of the APBDes with a GIS value of 0.029 < 0.05. And village financial management and internal control systems have a positive and significant effect on APBDes accountability with a sig value of 0.000 < 0.05.